Failure mechanisms in bone - a mechanical and histological study - Mercy, Matthew Vincent (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2006)
Repeated loading causes the development of microdamage in bone and may lead to failure by fatigue. Microdam age in the form of microcracks occurs naturally in bone due to the loads experienced during day-to-day activities, and unless such damage is repaired it can play a major role in the development of fragility and stress fractures. In order to maintain structural integrity this damaged bone must be replaced and it has been postulated that microdamage in bone acts as a stimulus for bone remodelling. The development of microdamage can be associated with the mechanisms of creep and fatigue. This study examined the effects of creep and fatigue, quantified the damage caused by these processes and considered the interaction between them. The influence of temperature on the damage caused by creep and fatigue was also investigated.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin